Beijing Central Asian Outbreak strain cluster of Mycobacterium tuberculosis detected in Irkutsk region, Russia - S. N. Zhdanova; I. G. Kondratov; O. V. Ogarkov (Acta Biomedica Scientifica, 2024)
Background. Irkutsk region maintains a high incidence rate of multidrug-resistant (MDR) tuberculosis (TB). Detection of MDR-associated Mycobacterium tuberculosis strains in Irkutsk region requires dynamic assessment of the TB pathogen population, taking into account the emergence of a new resistant variant of Beijing Central Asian Outbreak (CAO).The aim of the study. To assess changes in the genotypic structure of M. tuberculosis strains circulating in the Irkutsk region over a ten-year period.Materials and methods. A total of 732 M. tuberculosis strains (196 strains for 2021– 2022, 536 strains for 2011–2015) were studied using MIRU-VNTR and SNP typing.Results. The MDR level increased to 67.4 % with an increase of pre-extensive drug resistance (pre-XDR) (33.2 %) (p < 0.001). In the modern sample, the dominance of the Beijing genotype increased (83.7 %) due to an increase in the proportions of the B0/W148 (38.8 %) and CAO (12.8 %) subtypes with a stable overall level of Central Asian Russian (36.8 %) and other Beijing strains (8.2 %). Strains other than the Beijing genotype belonged mainly to the Euro-American lineage (Lineage 4): LAM (8.9 %), Ural (2.7 %), Haarlem (2.0 %), S (0.5 %) and L4-unclassified (5.3 %); 25 isolates were not classified. In the 2011–2015 sample, LAM was more common than in the modern sample (10.8 % vs. 3.6 %; p < 0.01). The increase in MDR and preXDR was statistically significant among Beijing B0/W148 strains (93.4 % vs. 66.1 %; p < 0.001).Conclusion. Unfavorable trends of significant spread of MDR and pre-XDR of the Beijing genotype strains were revealed. Among the Beijing strains, not only B0/W148 but also the Beijing CAO subtype, which was previously rare in Siberia, are the most successful; they have the highest levels of MDR and pre-XDR and a tendency to widespread distribution in all groups of TB patients.